Role of the prefrontal cortex in prosocial and self-maximization motivations: an rTMS study - Oksana Zinchenko; Olga Savelo; Vasily Klucharev (Scientific Reports, 2021)
Abstract More than a decade of neuroimaging and brain stimulation studies point to a crucial role for the right dorsolateral prefrontal cortex (rDLPFC) in prosocial behavior. The intuitive prosociality model postulates that the rDLPFC controls intuitive prosocial behavior, whereas the reflective model assumes that the rDLPFC controls selfish impulses during prosocial behavior. The intuitive prosociality model implies that the transient disruption of the rDLPFC should increase voluntary transfers in both dictator and generosity games. In contrast, the reflective model suggests that the transient disruption of the rDLPFC should decrease transfers in the dictator game, without affecting voluntary transfers in the generosity game, in which selfish motives are minimized. The aim of this paper was to compare predictions of the intuitive and reflective models using the classic dictator game and generosity game and continuous theta burst stimulation (cTBS). In this study, two groups of healthy participants (dictators) received either cTBS over the rDLPFC or right extrastriate visual areas. As shown by the results, the transient disruption of the rDLPFC significantly promoted prosocial motives in the dictator game only, particularly in the trials with the lowest dictator’s costs. These findings partially support the notion that the rDLPFC controls intuitive prosocial behavior.